Energy impact and eco-efficiency of the envelope insulation in residential buildings in Turkey - Evin, Duygu; Ucar, Aynur (Pergamon-Elsevier Science Ltd, 2019)
Approximately 31% of the energy requirement in Turkey is related to residential buildings. For this reason, residential buildings have an important role in reducing energy needs and greenhouse gas emissions. In this study, a procedure for determining the optimum thermal insulation thickness to be applied to the envelope (external walls, column, floor and roof) of residential buildings by using the heating-cooling energy requirement is presented. The heating and cooling loads and energy costs for different structures are calculated using the optimum thermal insulation thicknesses. Turkey is divided into four climatic zones in relation to their average temperature degree-days of heating according to the Turkish Thermal Insulation Standard. The methodology is applied to a residential building as a case study by comparing 4 insulation materials for 20 different energy demand scenarios for four different cities each representing a different climatic zone of Turkey. Once the global warming potential and cost indicators that is based on the Life Cycle Assessment have been obtained, the eco-efficiency analysis for each scenario are represented using eco-efficiency graphs.
Keywords: Thermal insulation; Optimum insulation thickness; Residential buildings; Envelope insulation; Eco-efficiency; Life cycle assessment